2017
DOI: 10.3906/elk-1701-19
|View full text |Cite
|
Sign up to set email alerts
|

Planar inverted-f antenna for universal serial bus dongle applications

Abstract: Abstract:A simple planar inverted-f antenna for universal serial bus dongles covering the frequency from 1.6 GHz to more than 3.6 GHz in a single band is presented in this paper

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…[11].Improved bandwidth has been achieved by controlling current distribution through the implementation of two vias in a printed PIFA of dimension 100 × 60 × 1.6 that resonated between 1.2 -3.0GHz [12]. A single-wideband 3D PIFA with size 55 × 20 × 3 covering frequency band from around 1.6 GHz to 3.6 GHz in one single band was presented in scientific literature [13]. It was reported that besides the variations in the dimensions and positions of the shorting and feeding plates, additional method of insertion of slot in the ground plane was used to enhance the overall bandwidth of the directional antenna for Universal Serial Bus (USB) applications [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11].Improved bandwidth has been achieved by controlling current distribution through the implementation of two vias in a printed PIFA of dimension 100 × 60 × 1.6 that resonated between 1.2 -3.0GHz [12]. A single-wideband 3D PIFA with size 55 × 20 × 3 covering frequency band from around 1.6 GHz to 3.6 GHz in one single band was presented in scientific literature [13]. It was reported that besides the variations in the dimensions and positions of the shorting and feeding plates, additional method of insertion of slot in the ground plane was used to enhance the overall bandwidth of the directional antenna for Universal Serial Bus (USB) applications [13].…”
Section: Introductionmentioning
confidence: 99%
“…A single-wideband 3D PIFA with size 55 × 20 × 3 covering frequency band from around 1.6 GHz to 3.6 GHz in one single band was presented in scientific literature [13]. It was reported that besides the variations in the dimensions and positions of the shorting and feeding plates, additional method of insertion of slot in the ground plane was used to enhance the overall bandwidth of the directional antenna for Universal Serial Bus (USB) applications [13]. To overcome the narrow bandwidth of PIFA at lower microwave frequency band, Muneer and his colleagues considered design of PIFA for higher microwave frequency band of 3.0 − 6.0 .…”
Section: Introductionmentioning
confidence: 99%